An Innovative Strategy for the Acquisition of Abstract Algebra in Higher Education: The Ethnomathematics Approach - Sri Suryanti; Li Long (Universitas Negeri Surabaya, 2025)
Abstract algebra learning in higher education is often perceived by students as abstract and difficult to understand. This results in low learning motivation and a lack of connection between algebraic concepts and the realities of everyday life. One approach that can be used to bridge this gap is ethnomathematics, namely the integration of local cultural values ​​​​in mathematics learning activities. This study aims to analyze the application of the ethnomathematics approach as an innovative strategy in abstract algebra learning and its impact on students' conceptual understanding, motivation, and learning attitudes. The research method used is a literature study by reviewing various previous empirical research results related to the application of ethnomathematics in mathematics education. The study's findings suggest that incorporating local cultural context into abstract algebraic concepts, including groups, rings, and areas, can enhance students' cognitive engagement, improve problem-solving abilities, and cultivate an appreciation for their own culture. This method could also make learning more meaningful and useful for students. So, ethnomathematics can be seen as a useful and new way to teach abstract algebra in college, and it can also help students become more mathematically literate by using local knowledge